2016
DOI: 10.1101/gr.210286.116
|View full text |Cite
|
Sign up to set email alerts
|

Detecting differential growth of microbial populations with Gaussian process regression

Abstract: Microbial growth curves are used to study differential effects of media, genetics, and stress on microbial population growth. Consequently, many modeling frameworks exist to capture microbial population growth measurements. However, current models are designed to quantify growth under conditions for which growth has a specific functional form. Extensions to these models are required to quantify the effects of perturbations, which often exhibit nonstandard growth curves. Rather than assume specific functional f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 68 publications
3
77
0
1
Order By: Relevance
“…The effects of stress and genetics on growth are then quantified by testing for statistically significant differences in the estimated parameters for different conditions ( 46 ). However, we previously showed that the impact of genetics and stress perturbations on growth are more accurately captured with a nonparametric Gaussian process (GP) model ( 35 ). In contrast to parametric models, GPs have the advantage of learning these relations directly from the data and do not require explicit equations describing the effects of stress and genetics on growth, which are typically unknown in the case of phenotypic discovery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of stress and genetics on growth are then quantified by testing for statistically significant differences in the estimated parameters for different conditions ( 46 ). However, we previously showed that the impact of genetics and stress perturbations on growth are more accurately captured with a nonparametric Gaussian process (GP) model ( 35 ). In contrast to parametric models, GPs have the advantage of learning these relations directly from the data and do not require explicit equations describing the effects of stress and genetics on growth, which are typically unknown in the case of phenotypic discovery.…”
Section: Resultsmentioning
confidence: 99%
“…A novel nonparametric model was developed using a Gaussian process framework to quantify these phenotypes. We used recently developed statistical tests ( 35 ) and developed new tests to identify significant differential growth between the trajectories of these TF knockouts relative to that of the control strain. The results revealed that a surprising number of TFs are required for optimal growth under multiple stress conditions, indicating a high level of interconnectivity within the GRN.…”
Section: Introductionmentioning
confidence: 99%
“…The significant increase in growth at 10 mM supplementation of trehalose indicates that the substitution may increase affinity of the PTS for trehalose transport, improve efficiency of transport, or increase expression and/or stability of the transporter however the role of the this E258D substitution in trehalose uptake still needs to be explored. Analysis of the growth curves by Gaussian Process modeling 38 allowed us to quantify growth rate, area under the curve, and carrying capacity of the isolates in each condition (Fig. 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…To describe and/or predict S-shaped growth curves, a number of mathematical models have been proposed, such as the Logistic (Verhulst, 1845; 1847) and Gompertz (Winsor, 1932) models, and revised and expanded repeatedly to better understand the biological process of bacterial growth under varied conditions (Fujikawa and Morozumi, 2005; Kargi, 2009; Koseki and Nonaka, 2012; Alonso et al, 2014; Desmond-Le Quemener and Bouchez, 2014; Hermsen et al, 2015). Although the growth curve of the most representative bacterium, Escherichia coli , has been examined since the 1930s (Winsor, 1932), the indescribable complexity of the growth dynamics of E. coli remain and are still under investigation with other models to understand the current differential growth dynamics (Swain et al, 2016; Tonner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%